The Crab House on Oyster Creek: Folkloristic Response to Vernacular Landscape and its Environmental Moorings - Chiarappa, Michael J. (Material Culture Review, 2021)
The Andersen crab house on Oyster Creek is located on a waterway that is part of the wider estuarine environment consisting of New Jersey’s Great Bay and the Mullica River. It is a building type that has long served oystermen, clammers, crabbers, finfishers, and waterfowlers along New Jersey’s Atlantic Ocean and Delaware Bay coastlines. Having survived for almost ninety years, the building’s siting allows Phil Andersen to effectively tend the adjacent crabbing grounds and prepare the catch for market. The building, along with his boat and harvesting gear organizes the contours of his working landscape, tools that do not simply define the occupation’s environmental fit, but, as an assemblage, continually advance Andersen’s acquisition of traditional ecological knowledge. While its stark presence on the salt marsh punctuates its environmental fit and role as the axis of Andersen’s occupational map, its enduring function as a working landscape resonates widely throughout the community. The work and social life of the building speak to its capacity to be broadly affiliative, its features, use, and siting laden with aesthetic and performative depth that make it a touchstone of environmental experience and sense of place. These attributes—specifically their role in curating memory and affirming a community’s environmental moorings—show how the Andersen crab house, and similar buildings that preceded it, have engendered folkloristic response for over one hundred and fifty years.